COMPREHENSIVE REVIEW OF RADIOLOGICAL IMAGING TECHNIQUES AND ANESTHESIA SUPPORT IN SURGERY - Almutairi, Afrah Hamdan; Alshammas, Norah; Sulaiman, Nada; Aljehani, Bothaina Ahmed; Al.jarie, Atheer; Alshehri, Mohamed; Alonazi, Amal Ayed; Alswihib, Munera Saad; Almaliki, Abdulwahab Saeed; Alnazi, Khalaf Sulaiman (Journal of Ecohumanism, 2024)
This review gives a synthesis of the applications of radiological imaging and anesthesia during surgeries. It examines how modalities like X-ray, CT, MRS, and ultrasound have changed the face of surgery by furnishing vital information for the identification of the type and extent of the surgical problem, planning of the surgery, and during the surgery operation. The paper also considers changes in forms of anesthesia support, including general, regional, and local anesthesia, and how, when used in conjunction with imaging, they can improve patient safety and comfort as well as surgical outcomes. Among the issues discussed are the prospects for and difficulties in the two fields, as well as suggestions on how one might enhance the success rate of surgery and the quality of treatment.